Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Choose the equation below that represents the line passing through the point [tex]\((-2, -3)\)[/tex] with a slope of -6.

A. [tex]\(y + 3 = -6(x + 2)\)[/tex]

B. [tex]\(y + 2 = 6(x + 3)\)[/tex]

C. [tex]\(y - 3 = -6(x - 2)\)[/tex]

D. [tex]\(y - 2 = 6(x - 3)\)[/tex]


Sagot :

To determine which equation represents the line passing through the point [tex]\((-2, -3)\)[/tex] with a slope of [tex]\(-6\)[/tex], we can use the point-slope form of a linear equation. The point-slope form is given by:

[tex]\[ y - y_1 = m(x - x_1) \][/tex]

where [tex]\((x_1, y_1)\)[/tex] is a point on the line, and [tex]\(m\)[/tex] is the slope of the line. Let's apply the given point [tex]\((-2, -3)\)[/tex] and the slope [tex]\(-6\)[/tex].

1. Substitute the given point and slope into the point-slope form:

[tex]\[ y - (-3) = -6(x - (-2)) \][/tex]

2. Simplify the equation:

[tex]\[ y + 3 = -6(x + 2) \][/tex]

Hence, the equation that represents the line passing through the point [tex]\((-2, -3)\)[/tex] with a slope of [tex]\(-6\)[/tex] is:

[tex]\[ y + 3 = -6(x + 2) \][/tex]

We can now match this equation with the given options:

1. [tex]\(y+3=-6(x+2)\)[/tex]
2. [tex]\(y+2=6(x+3)\)[/tex]
3. [tex]\(y-3=-6(x-2)\)[/tex]
4. [tex]\(y-2=6(x-3)\)[/tex]

The correct equation is option 1:

[tex]\[ y+3=-6(x+2) \][/tex]

Therefore, the answer is the first option.